2019
DOI: 10.31744/einstein_journal/2019ao4725
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions among older adults followed up in a comprehensive medication management service at Primary Care

Abstract: Objective: To estimate the prevalence of drug interactions and associated factors among older adults followed up in a Comprehensive Medication Management Service at Primary Care. Methods: Firstly, the Beers criteria 2015 was used to define drug interactions; later, drug interactions proposed by Dumbreck for patients with diabetes, depression, and heart failure were evaluated. The associated factors were assessed by univariate (Pearson's χ 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…18,19 On the other hand, the older age detected causes concern, since the mean of potential DI identified was high (95.5%), and DI tend pose more threats to this population due to the considerable pharmacokinetic and pharmacodynamic changes caused by the aging process that can potentialize their adverse clinical consequences. [20][21][22] The mean of DI encountered (mean= 5.9 DI/patient) was, however, similar to that found in other studies 22,23 , and involved mainly the most commonly used drugs among the study's patients, as expected.…”
Section: Unnecessary Drugssupporting
confidence: 86%
See 3 more Smart Citations
“…18,19 On the other hand, the older age detected causes concern, since the mean of potential DI identified was high (95.5%), and DI tend pose more threats to this population due to the considerable pharmacokinetic and pharmacodynamic changes caused by the aging process that can potentialize their adverse clinical consequences. [20][21][22] The mean of DI encountered (mean= 5.9 DI/patient) was, however, similar to that found in other studies 22,23 , and involved mainly the most commonly used drugs among the study's patients, as expected.…”
Section: Unnecessary Drugssupporting
confidence: 86%
“…Therefore, the CMM service contributes to the deprescription of medications by proposing the suspension of those that are unnecessary, in order to avoid the patient experiencing adverse reactions (including those caused by DI) without any benefit in the use of the drug. 11,21 Our study showed that it is fundamental to analyze the DI in a clinically contextualized manner. Also, professionals who intend to perform such analysis should distinguish the DI that can be monitored from those that are not monitorable.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Most studies (n = 23) used a cross-sectional design. Studies ranged in [20,22,46,[48][49][50][51][52][53][54][55][56][57][58][59][60][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] reported DDI prevalence estimates using study participants as the unit of analysis, one study [75] also reported DDI prevalence using the total number of prescriptions as the unit of analysis, and one study [64] also reported DDI prevalence using the total number of drugs as the unit of analysis. One study [61] only reported the total number of drug combinations potentially leading to serious DDIs, and one study [47] only reported the proportion of PIMs that were due to DDIs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%